2012
DOI: 10.1073/pnas.1113736109
|View full text |Cite
|
Sign up to set email alerts
|

β3 integrin interacts directly with GluA2 AMPA receptor subunit and regulates AMPA receptor expression in hippocampal neurons

Abstract: The integrins are transmembrane receptors for ECM proteins, and they regulate various cellular functions in the central nervous system. In hippocampal neurons, the β3 integrin subtype is required for homeostatic synaptic scaling of AMPA receptors (AMPARs) induced by chronic activity deprivation. The surface level of β3 integrin in postsynaptic neurons directly correlates with synaptic strength and the abundance of synaptic GluA2 AMPAR subunit. Although these observations suggest a functional link between β3 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 50 publications
1
71
0
Order By: Relevance
“…Importantly, blocking the synaptic removal of GluA2-containing CI-AMPARs during retrieval prevented this AMPAR composition exchange, and also protected the consolidated memory against becoming labile. Because GluA2 stabilizes dendritic spines (26,28) and retains AMPARs at synapses through direct interaction with synaptic proteins (11,(23)(24)(25)(26)(27), the loss of CI-AMPARs may destabilize potentiated synaptic strength, and hence memory. Our results suggest that other manipulations leading to synaptic removal of CI-AMPARs may destabilize consolidated memory as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, blocking the synaptic removal of GluA2-containing CI-AMPARs during retrieval prevented this AMPAR composition exchange, and also protected the consolidated memory against becoming labile. Because GluA2 stabilizes dendritic spines (26,28) and retains AMPARs at synapses through direct interaction with synaptic proteins (11,(23)(24)(25)(26)(27), the loss of CI-AMPARs may destabilize potentiated synaptic strength, and hence memory. Our results suggest that other manipulations leading to synaptic removal of CI-AMPARs may destabilize consolidated memory as well.…”
Section: Discussionmentioning
confidence: 99%
“…Given that GluA2 stabilizes AMPARs at synapses through interaction with synaptic proteins (11,(23)(24)(25)(26)(27) and also stabilizes dendritic spines (26,28), supporting memory storage (29)(30)(31), CI-AMPAR endocytosis may destabilize the potentiated synaptic strength underlying consolidated memory. We tested whether the memory retrievalinduced decrease in CI-AMPARs is critical for rendering the memory unstable using GluA2 3Y .…”
Section: Blocking Of Ci-ampar Endocytosis Prevents Transformation Of Amentioning
confidence: 99%
“…Here, we found that brief PIKfyve inhibition during NMDA stimulation blocks internalization of GluA2 and that PIKfyve inhibition immediately following NMDA stimulation hastens the recovery of surface GluA2 levels after internalization. The GluA2 subunit plays an instructive role in homeostatic plasticity induced by chronic changes in activity (67,69,78,79,83,84), thereby providing a potential link between PI(3,5)P 2 synthesis during sustained activity changes and the regulation of AMPAR expression at the cell surface. Our results are consistent with up-regulation of PI(3,5)P 2 levels driving AMPAR internalization and PI(3,5)P 2 acting by delaying or diverting internalized receptors from recycling back to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin receptors and ion channels communicate by diffusible signals (16)(17)(18)(19)(20) as well as by forming macromolecular complexes (21)(22)(23)(24)(25). In particular, the b 1 integrin-mediated adhesion to fibronectin activates hERG1 currents (I hERG1 ) in different cell types (17,26).…”
Section: Introductionmentioning
confidence: 99%